One-Year Changes in Urinary Microbial Phenolic Metabolites and the Risk of Type 2 Diabetes—A Case-Control Study - Marhuenda-Muñoz, María; Domínguez-López, Inés; Laveriano-Santos, Emily P.; Parilli-Moser, Isabella; Razquin, Cristina; Ruiz-Canela, Miguel; Basterra-Gortari, Francisco Javier; Corella, Dolores; Salas-Salvadó, Jordi; Fitó, Montserrat; Lapetra, José; Arós, Fernando; et al. (IOAP-MPDI, 2022)
The intake of polyphenols has been associated with a risk reduction of type 2 diabetes. Nevertheless, to the best of our knowledge, the molecules that might be metabolically active after ingestion are only starting to be investigated regarding this metabolic disease. To investigate the association between one-year changes in urinary microbial phenolic metabolites (MPM) and the incidence of type 2 diabetes, we performed a case-control study using data and samples of the PREDIMED trial including 46 incident type 2 diabetes cases of 172 randomly selected participants. Eight urinary MPMs were quantified in urine by liquid chromatography coupled to mass spectrometry and used to assess their associations with type 2 diabetes risk by multivariable logistic regression models. Compared to participants in the lowest tertile of one-year changes in hydroxybenzoic acid glucuronide, those in the highest tertile had a significantly lowered probability of developing type 2 diabetes (OR [95% CI], 0.39 [0.23–0.64]; p < 0.001 for trend). However, when additionally adjusting for fasting plasma glucose, the statistical significance was lost. Changes in the dietary pattern can increase the concentrations of this compound, derived from many (poly)phenol-rich foods, and might be changing the gut microbial population as well, promoting the production of the metabolite.
Keywords: Sustancias fitoquímicas; Bioactive compounds; Phytochemicals; Mediterranean diet; PREDIMED study; Urinary microbial phenolic metabolites; Cardiovascular; Liquid chromatography; Mass spectrometry